2011
DOI: 10.1249/mss.0b013e31820750f5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Energy Expenditure in Male Endurance Athletes

Abstract: According to our results, the SWA does not provide valid results of TEE and ExEE in endurance athletes because of the underestimation of EE at higher exercise intensities. It seems necessary to develop exercise-specific prediction equations to improve EE measurements in athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
76
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 36 publications
13
76
1
1
Order By: Relevance
“…Subjects performed 3 separate bouts of 10-minute treadmill running at different intensities (65%, 75%, and 85%), in addition to a 30-minute self-paced outdoor run. When the SWA Armband was compared to the IC system, results indicated that the SWA Armband significantly underestimated EE at intensities above 10 MET's, or a running speed of 6 mph (22 Previous studies reveal a lack of consistency when the SWA measures energy expenditure (31,22,39,40,78,43,51,52), suggesting further exploration of the accuracy in the SWA method at varying exercise intensities is warranted. Furthermore, it is possible that additional algorithms modeled for athletes or higher intensity exercise maybe needed to improve the estimation of EE from the SWA technique.…”
Section: Validation Studies Conducted In Adultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Subjects performed 3 separate bouts of 10-minute treadmill running at different intensities (65%, 75%, and 85%), in addition to a 30-minute self-paced outdoor run. When the SWA Armband was compared to the IC system, results indicated that the SWA Armband significantly underestimated EE at intensities above 10 MET's, or a running speed of 6 mph (22 Previous studies reveal a lack of consistency when the SWA measures energy expenditure (31,22,39,40,78,43,51,52), suggesting further exploration of the accuracy in the SWA method at varying exercise intensities is warranted. Furthermore, it is possible that additional algorithms modeled for athletes or higher intensity exercise maybe needed to improve the estimation of EE from the SWA technique.…”
Section: Validation Studies Conducted In Adultsmentioning
confidence: 98%
“…Although considered accurate, the Mini may overestimate or underestimate the energy cost for certain physical activities (22,31,39,40,43,78). The accuracy of the armband is also reliant on population or activity specific algorithms (3).…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations